Bioactivity and Benefits of the Okra Plant (Abelmoschus Esculentus (L.) Moench.) : Literature Review - Tri Putri Wahyuni; Atyka Trianisa (CV. Get Press Indonesia, 2024)
Abelmoschus esculentus L., commonly known as okra, is a flowering plant belonging to the Malvaceae family. Okra is a versatile plant due to the various uses of its fresh leaves, buds, flowers, pods, stems, and seeds. Okra is a popular health food because of its high content of fiber, vitamin C, and folate, as well as being a good source of calcium and potassium. Additionally, this plant has been used medicinally in the treatment of several disorders, demonstrating anti-cancer, antimicrobial, hypoglycemic, and anti-ulcer activities. Okra is a vegetable crop with diverse nutritional qualities and potential health benefits. This plant is also known to be high in antioxidants. The purpose of this research is to investigate bioactivities such as antioxidant, anti-cancer, antibacterial, and antidiabetic activities, as well as to determine the benefits of okra.